Integrative Transcriptomic and Small RNA Sequencing Reveals Immune-Related miRNA–mRNA Regulation Network for Soybean Meal-Induced Enteritis in Hybrid Grouper, Epinephelus fuscoguttatus♀ × Epinephelus lanceolatus♂ - He, Yuanfa; Ye, Guanlin; Chi, Shuyan; Tan, Beiping; Dong, Xiaohui; Yang, Qihui; Liu, Hongyu; Zhang, Shuang (Frontiers in Immunology, 2020)
A 10-week feeding experiment was conducted to reveal the immune mechanism for soybean meal-induced enteritis (SBMIE) in hybrid grouper, Epinephelus fuscoguttatus♀ × Epinephelus lanceolatus♂. Four isonitrogenous and isolipidic diets were formulated by replacing 0%, 10%, 30%, and 50% fish meal protein with soybean meal (namely FM, SBM10, SBM30, and SBM50, respectively). Weight gain rate of the SBM50 group was significantly lower compared with other groups. Plica height, muscular layer thickness, and goblet cells of the distal intestine in the SBM50 group were extremely lower than those in the FM group. The intestinal transcriptomic data, including transcriptome and miRNAome, showed that a total of 6,390 differentially expressed genes (DEGs) and 92 DEmiRNAs were identified in SBM50 and FM groups. DEmiRNAs (10 known and 1 novel miRNAs) and their DE target genes involved in immune-related phagosome, natural killer cell-mediated cytotoxicity, Fc gamma R-mediated phagocytosis, and the intestinal immune network for IgA production pathways. Our study is first to offer the transcriptomic and small RNA profiling for the SBMIE in hybrid grouper. Our findings offer important insights for the understanding of the RNA profile and further elucidation of the underlying molecular immune mechanism for the SBMIE in carnivorous fish.